L’Approche Orientée Objets ou l’EuroWordNet ? Quelle approche pour la traduction automatique? Partie II: hiérarchie, héritage et désambiguïsation - Szramek-Karcz, Sonia (Neophilologica, 2014)
The presentation of research results concerning applicability of AOO and EWN in machine translation is divided into two parts. In the first part, the author presents the influence of databases design, their theoretical aspects and the categorization of lexical items on the process and result of machine translation. The second part is devoted to the internal hierarchy of databases including the established categorization of lexical items as well as semantic inheritance comprising multiple inheritance and disambiguation accomplished by the above mentioned databases. The presented results coupled with the capability of contemporary computer technology give grounds for claiming that a bilingual approach in lexical description for machine translation is the best choice.